Exploration of the profile-effect relationship of Siraitia grosvenorii aqueous extracts related to their laxative effect on the basis of gray correlation analysis - Wei Dong; Jia Zeng; Qin Wang; Xin Jiang; Ting Huang (BMC, 2021)
Abstract Background Siraitia grosvenorii (binomial name Siraitia grosvenorii (Swingle) C. Jeffrey ex Lu et Z. Y. Zhang), also called Arhat Fruit or Monk's Fruit, is a dried ripe fruit belonging to the Cucurbitaceae Family. S. grosvenorii has a long history of being used for constipation treatment in folk medicine. However, there are few studies where the laxative effect, related mechanisms, and active constituents of S. grosvenorii were investigated. This research explores the relationship between the common components and the laxative effect of aqueous extracts of S. grosvenorii from different habitats in China. Methods The fingerprints of S. grosvenorii aqueous extracts from different habitats were established by HPLC. The constipation mice model was used to investigate the laxative effect of S. grosvenorii aqueous extracts. The motilin (MTL) level in mice serum, and the water content of the large and small intestines in mice were determined. The profile-effect relationship of S. grosvenorii aqueous extracts was preliminarily clarified using gray correlation analysis. Results Nine common peaks were identified from the fingerprint of aqueous extracts of S. grosvenorii. The aqueous extracts obviously shortened the incubation period of defecation, and significantly increased the number of defecations, and the wet and dry weight of defecation in constipated mice. The profile-effect relationship indicated that seven common peaks were highly correlated with the effect of the incubation period of defecation, the number of defecations, and the wet and dry weight of defecation in mice. Conclusion This work provides a promising method for the fingerprint establishment, pharmacodynamic evaluation, and quality control of S. grosvenorii on the basis of its profile-effect relationship.